Theoretical and Experimental Investigation of Gamma Shielding Properties of TiO2 and PbO Coated Glasses - COŞKUN, Arzu; ÇETİN, Betül; YİĞİTOĞLU, İbrahim; CANIMKURBEY, Betül (International Journal of Computational and Experimental Science and Engineering, 2023)
This manuscript has investigated the effect of TiO2 and PbO-coated glasses on radiation absorption properties to develop alternative materials for radiation shielding. The shielding properties of glass materials coated with oxides were calculated experimentally with a gamma spectrometer with NaI(Tl) detector and theoretically with the XCOM computer program and GATE simulation program. Within this scope, the shielding properties of TiO2, Pb0, and Pb0 doped TiO2 glasses at 511, 662, 1274 keV gamma energies were calculated. The results obtained showed that 50% Pb0 contribution can increase the shielding properties of TiO2 glasses. Also, it has been observed that the experimental and theoretical results obtained are compatible with each other.